Socio-sexual norms and young people's sexual health in urban Bangladesh, India, Nepal and Pakistan: A qualitative scoping review. - Prima Alam; Leesa Lin; Nandan Thakkar; Abhi Thaker; Cicely Marston (PLOS Global Public Health)
In South Asia, young people face myriad challenges and opportunities regarding their sexual lives relating to varied experiences of norms and restrictions; gender norms and socio-sexual taboos limit communication around sexual health which in turn can affect sexual health outcomes. In this article we focus on norms affecting young people's sexual health experiences in urban settings in Bangladesh, India, Nepal, and Pakistan. We conducted a scoping review of peer reviewed empirical studies based on qualitative data pertaining to young people's experiences of sexuality and sexual health in Bangladesh, India, Nepal, and Pakistan. We searched four electronic databases for articles published (2010-2022), using terms relating to sexual health, young people, and South Asia. Sixteen articles met the inclusion criteria with sample size ranging from 9 to 180. The authors followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) guidelines for the design and analysis of this study. We synthesised the included articles using thematic analysis. The studies covered topics such as sexual health services and contraceptive use; sexuality education and communication; and gender and sexual violence. Recurring findings included: parental and societal expectations around premarital 'sexual purity' through abstinence; limited communication around sexuality between young people and parents/adults; gender norms limiting young women's sexual and reproductive decision making; and an absence of research on experiences of sexual and gender minorities. We identified common themes as well as prominent gaps which must be addressed if we are to capture diverse experiences and build a better evidence base to improve sexual health services for young people in the region. The body of research fails to include experiences of young people with diverse gender, sexual orientation, and sex characteristics.